2011
DOI: 10.2298/jsc100118005l
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Cu2+ and Co2+ ions from aqueous solutions onto sepiolite: An equilibrium, kinetic and thermodynamic study

Abstract: The efficiency of natural sepiolite for the removal of Cu 2+ and Co 2+ from aqueous solution was determined using the batch method. The sorption experiments were performed as a function of the initial metal concentration, the equilibration time and temperature. Thermodynamic parameters, such as enthalpy, free energy and entropy, were calculated from the temperature dependent sorption isotherms and these values showed that the sorption of the investigated metals onto sepiolite was endothermic. The pseudo-second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, iron(III)−modified sepiolite has not previously been used for arsenic sorption from aqueous media. The obtained suspension was diluted to 2 dm 3 and then heated to 70 °C for 48 h. The precipitate was washed, dried and used as the sorbent, designated as Fe-SEP. 15 XRD analysis, FTIR spectroscopy and DTA/TGA 15 confirmed that Fe-SEP maintained the basic structure of sepiolite. The presence of new crystalline Fe phases was not observed, indicating that only amorphous Fe species were present.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…To the best of our knowledge, iron(III)−modified sepiolite has not previously been used for arsenic sorption from aqueous media. The obtained suspension was diluted to 2 dm 3 and then heated to 70 °C for 48 h. The precipitate was washed, dried and used as the sorbent, designated as Fe-SEP. 15 XRD analysis, FTIR spectroscopy and DTA/TGA 15 confirmed that Fe-SEP maintained the basic structure of sepiolite. The presence of new crystalline Fe phases was not observed, indicating that only amorphous Fe species were present.…”
Section: Introductionmentioning
confidence: 75%
“…A solution could lie in the deposition of Fe(III) oxyhydroxides on porous minerals, such as zeolites, bentonites and sepiolites. 5,7,8,[14][15][16][17] Sepiolite is a fibrous hydrated magnesium silicate 18,19 with a unit cell formula Mg 8 Si 12 O 30 (OH) 4 (H 2 O) 4 ·nH 2 O, n = 6−8. Their structures have blocks and channels running parallel to the fibre axis, which provide excellent potential for the retention of micropollutants from water.…”
Section: Introductionmentioning
confidence: 99%
“…Since clay minerals are already known to be efficient sorbent of various pollutants [9][10][11][12][13][14][15][16][17][18], bentonite was also used for the Zn 2+ removal from aqueous solution [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus the surface complexes occurs between the copper species and the negatively charged adsorbent [40] (Scheme 1).…”
Section: Adsorption Mechanismmentioning
confidence: 99%